Recurrence of Pemphigus Vulgaris after Bilateral Breast Irradiation: A Case Report and Review of the Literature - Camille Invernizzi (Karger Publishers, 2021)
Pemphigus is a serious and rare chronic bullous autoimmune disease. It is characterized by mucocutaneous erosions secondary to autoantibodies directed against desmogleins 1 and 3, proteins involved in intercellular adhesion mechanisms. The occurrence of pemphigus is based on the triggering of genetic and external environmental factors such as drugs, infection, and more rarely radiotherapy. To date, only 16 cases of radiation-induced pemphigus are described in the context of breast cancer treatment. We present the case of a 76-year-old woman who had a recurrence of pemphigus vulgaris limited to the irradiation field after exposure to an adjuvant radiotherapy treatment for a bilateral triple-negative breast cancer. The onset was bilateral limited to the irradiation area and was treated effectively with local and systemic corticosteroids. After a rigorous review of the literature, only 16 cases of breast cancer radiation-induced pemphigus appeared. In contrast to several cases, the rash was limited to the irradiated area and improved with systemic corticosteroids. For more than three-quarters of the described cases in the literature, pemphigus occurs within 3 months following the end of treatment. After systemic immunosuppressive treatment, this disease disappears in the vast majority of the reported cases.